PENGEMBANGAN GAME EDUKASI “MALAYA” UNTUK PENGENALAN TATA SURYA BERBASIS ANDROID PADA SD NEGERI 33 PAGAR ALAM - Lendy Rahmadi; Medi Triawan; Mira Rosalena (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
Learning about the solar system for elementary school students is still manual using textbooks or lecture methods, which is one of the problems that makes students less active in the learning process. Therefore, new learning methods are needed to increase the interest in learning of class VI students at SD Negeri 33 Pagar Alam. One way to increase students' interest in learning is to change the learning method to be more interesting and not boring, so an Android-based educational game introducing the solar system is created so that Class VI students are more enthusiastic about playing while learning. The development of this game uses the GDLC (Game Development Life Cycle) method. The use of educational games as an alternative medium in delivering material is considered effective and efficient because games are generally often played and liked by elementary school children, so an Android-based educational game introducing the solar system elementary school was created. By making this educational game, it can make it easier for students to understand the solar system, especially knowing the names of the planets in the solar system.